Preterm infant meconium microbiota transplant induces growth failure, inflammatory activation, and metabolic disturbances in germ-free mice - Henni Hiltunen (Elsevier, 2021)
Summary: Preterm birth may result in adverse health outcomes. Very preterm infants typically exhibit postnatal growth restriction, metabolic disturbances, and exaggerated inflammatory responses. We investigated the differences in the meconium microbiota composition between very preterm (<32 weeks), moderately preterm (32–37 weeks), and term (>37 weeks) human neonates by 16S rRNA gene sequencing. Human meconium microbiota transplants to germ-free mice were conducted to investigate whether the meconium microbiota is causally related to the preterm infant phenotype in an experimental model. Our results indicate that very preterm birth is associated with a distinct meconium microbiota composition. Fecal microbiota transplant of very preterm infant meconium results in impaired growth, altered intestinal immune function, and metabolic parameters as compared to term infant meconium transplants in germ-free mice. This finding suggests that measures aiming to minimize the long-term adverse consequences of very preterm birth should be commenced during pregnancy or directly after birth.